Studi Perbandingan Hasil Pengukuran Alat Teodolit Digital dan Manual: Studi Kasus Pemetaan Situasi Kampus Kijang - Suhendra, Andryan (Bina Nusantara University, 2011)
Ground measurement helps illustrate a situation of land map to ease a civil engineer determining the center point of a building. From the situation map can determined the further works such as determining the point of building, land leveling, determining the point of the foundation and the volume of work for hoarding the land. A tool used for measurement activities is theodolite. Theodolite serves as a tool to determine the angle formed between the two points at the time of measurement. Drawing a situation map requires the results of the point measurement data. Theodolite is divided into two types, digital and manual. This study compares measurements results using both digital and manual theodolite performed at Kijang Campus, Binus University. From the comparison of data processing generated large differences in the coordinate system on the situation map with ranging from 1.31% to 322.67% on the abscissa axis and 0.39% to 41.83% on the ordinate axis.